Strategic Learning and Metacognitive Skills in Mathematics of The Bachelor of Industrial Technology at A University in Roxas City, Capiz - Icamina, Princess May A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Students frequently believe that mathematics is a challenging subject to learn. The learners must have the necessary skills to study the material quickly as a result. The idea that learners can select various methods for completing particular tasks is implied frequently by the term "strategic learning skills". This strategy can help students develop their critical-thinking and artistic abilities in the classroom. The investigation aims to determine the level of strategic learning skills of students that affect their level of metacognitive skills in Mathematics. The study used the survey-correlational method of research in gathering data. The participants of this study were the 158 BS in Industrial Technology second-year students, officially enrolled in Capiz State University – Main Campus randomly selected using stratified sampling. Data were gathered using a 50-item researcher-made Strategic Learning Skills Questionnaire and a 35-item standardized Metacognitive Skills Questionnaire. Frequency count, percentage, mean, standard deviation, One-way ANOVA, and Pearson r were used as statistical tools. Inferential tests were at the alpha level of significance set at 0.05. Findings revealed that the level of strategic learning skills of the second-year learners of the BS in Industrial Technology was “high”. In consonance, the level of their metacognitive skills in Mathematics was “evident”. These led to the conclusion that there were no appreciable differences in the metacognitive abilities among the strategic learning skill levels of the second-year BS in Industrial Technology learners. There was no connection between the second-year students of BS in Industrial Technology's strategic learning and metacognitive skills in Mathematics.